Korespondencja (1954)
Listy od następujących, Wil.-Win.:
a 1978 601
Keywords: Bydgoszcz; m.; Państwowe Teatry Ziemi Pomorskiej; Scena Bydgoska (Winter); m.; Państwowy Teatr Polski (Winnicka); Kalisz; m.; Państwowy Teatr im. W. Bogusławskiego (Winkler); Teatr polski 20 w.; Teatr polski zob. też dramaty; opera; programy; recenzje